Structural and electrochemical properties of 20-micron Li(Co1−xLix)O2−δ (x>0) agglomerates with layered structures: Identification of tetravalent cobalt. (December 2015) - Mishima, Y.; Hojo, T.; Nishio, T.; Kajiyama, A.; Moriyoshi, C.; Kuroiwa, Y.
Abstract: The increasing demand for the high energy density of lithium-ion batteries gives rise to the development of larger particle sizes of the active electrode materials. 20 μm-sized Li(Co1− x Li x )O2− δ agglomerates are synthesized via solid-state reactions with different nominal compositions (Li/Co=1.00, 1.02, and 1.05) at 1000 °C for 5 h in ambient air while suppressing the lithium vaporization. Careful inductively coupled plasma and iodometric measurements indicate the existence of tetravalent cobalt in the solid solutions ( x >0). The decreasing ideal capacity with the increasing x value could cause the resulting initial capacities at under a quasi-equilibrium condition. The defect structure is also discussed in terms of the structural parameters calculated from Rietveld refinements of the high-energy synchrotron-radiation powder-diffraction data. Highlights: 20 μm size-controlled Li(Co1− x Li x )O2 − δ agglomerates were synthesized. Careful chemical analyses showed the Co 4+ ions of the agglomerates. Resulting initial capacities are quantitatively explained by the ideal ones. High-energy synchrotron-radiation powder-diffraction data were analyzed. The accurate structural parameters support the results of the chemical analyses.